ChemInform Abstract: Graphene Oxide Catalyzed C—H Bond Activation: The Importance of Oxygen Functional Groups for Biaryl Construction. Issue 26 (June 2016) - Gao, Yongjun; Tang, Pei; Zhou, Hu; Zhang, Wei; Yang, Hanjun; Yan, Ning; Hu, Gang; Mei, Donghai; Wang, Jianguo; Ma, Ding
Abstract: The oxygen sites in the graphene oxide catalyst and the addition of potassium tert‐butoxide are found to be essential for this novel direct C—H arylation method.